KEABSAHAN PERJANJIAN KERJA WAKTU TERTENTU TANPA METERAI SERTA AKIBAT HUKUMNYA - Evy Savitri Gani (IAIN Ambon, 2018)
Communities often assume that employment agreements signed without materei are illegal and therefore are not recognized. In law, the purpose of the covenant is to prove the existence of a legal event forming a legal relationship between the parties (the engagement). So here is the relationship between workers and employers. In certain time labor agreements made for the benefit of such proofs, stamp duty is not a legitimate requirement, so the absence of stamp duty does not result in a specified time period of employment being invalid. Because the legitimate requirements of the agreement contained in Article 1320 of the Civil Code and Article 52 of Act 13 of 2003 on Manpower does not require stamp duty. Thus the legal consequence of the absence of seal is that the agreement remains binding on the parties making it, but if the agreement or document is to be used before the court as a proof then it can be done later. Key words: legitimacy, work agreement specifictime, stamp duty, legal effect